2008
DOI: 10.1101/gad.1703108
|View full text |Cite
|
Sign up to set email alerts
|

Defining the regulatory network of the tissue-specific splicing factors Fox-1 and Fox-2

Abstract: The precise regulation of many alternative splicing (AS) events by specific splicing factors is essential to determine tissue types and developmental stages. However, the molecular basis of tissue-specific AS regulation and the properties of splicing regulatory networks (SRNs) are poorly understood. Here we comprehensively predict the targets of the brain-and muscle-specific splicing factor Fox-1 (A2BP1) and its paralog Fox-2 (RBM9) and systematically define the corresponding SRNs genome-wide. Fox-1/2 are cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
294
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(331 citation statements)
references
References 62 publications
36
294
0
1
Order By: Relevance
“…We again used the MS2-tethering assay to examine RBFOX1's activity in exon repression. We modified a b-globin PB1 minigene (Zhang et al 2008) to address this question. We mutated the three natural RBFOX1 motifs in the upstream intron, as well as two motifs in the exon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We again used the MS2-tethering assay to examine RBFOX1's activity in exon repression. We modified a b-globin PB1 minigene (Zhang et al 2008) to address this question. We mutated the three natural RBFOX1 motifs in the upstream intron, as well as two motifs in the exon.…”
Section: Resultsmentioning
confidence: 99%
“…Global analysis was utilized more recently to evaluate the splicing regulatory networks of the RBFOX family of proteins. A combination of microarray, CLIP-seq, high-throughput RT-PCR, and computational analyses by different laboratories resulted in the identification of many endogenous target genes, and confirmed the so-called ''RNA map,'' meaning that the splicing outcome (activation or repression) depends in a predictable manner on the location of the UGCAUG element (Zhang et al 2008;Venables et al 2009;Yeo et al 2009). Certain other splicing factors, such as Nova and PTB, also have a similar map with position-dependent activities (Ule et al 2006;Llorian et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Altogether, in vivo and ex vivo analyses demonstrated that the c.820 þ 13A4G variation is actually a disease-causing mutation. Our results, neatly complemented by the in vivo analysis of patients' cells, reiterate the reliability of the ex vivo minigene functional assay to unravel the molecular mechanism(s) whereby a variation affects splicing.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, many of the predicted Rbfox2 alternatively spliced target transcripts themselves encoded splicing factors, suggesting the possibility of a higher-order regulatory network. Gene ontology (GO) analysis of the Rbfox2 splicing regulatory network demonstrated enrichment of a biologically coherent set of transcripts encoding proteins mediating synaptic transmission and membrane excitability [77,78]. Genome-wide analysis of brain RNA of Rbfox2 knock-out mice identified numerous splicing changes altering proteins important both for brain development and mature neuronal function.…”
Section: Rbfox Familymentioning
confidence: 99%